Altered gene expression profile of Wolbachia pipientis wAlbB strain following transinfection from its native host Aedes albopictus to Aedes aegypti cells. Issue 6 (7th January 2021) - Bishop, Cameron; Asgari, Sassan
Abstract: Wolbachia is an obligate intracellular bacterial symbiont prevalent among arthropods and nematodes. To survive and reproduce, Wolbachia interacts with and modifies host subcellular structures, while sensing and responding to changes within the cellular environment. In mutualistic associations, Wolbachia may provision the host with metabolites, or help to maintain the chemical homeostasis of the host cell. Some strains can rapidly invade insect populations by manipulating host reproductive biology, while also preventing viral replication, allowing their use in vector control of arthropod‐borne viruses. The Aedes albopictu s‐derived strain w AlbB is promising in this regard. When transinfected into the Yellow fever mosquito, Aedes aegypti, w AlbB reaches high frequencies within wild populations, and strongly inhibits viral transmission. Despite its obvious potential, much is still unknown about the molecular interactions between Wolbachia and host that enable its use in vector control. Furthermore, most Wolbachia transinfection research to date has focused on host effects. In the current study, we used a cell line model to explore the effect of transinfection of w AlbB from Ae . albopictus to Ae . aegypti . Using RNA sequencing, we show that several genes associated with host‐symbiont interactions were downregulated by transinfection, with the greatest downregulation exhibited by prophage‐associated genes. Abstract : In this study, w AlbB strain of Wolbachia was transinfected from Aedes albopictus Aa23 cells into Aedes aegypti Aag2 cells. RNA‐Seq of Aa23 and Aag2. w AlbB cells showed differential expression of a number of w AlbB genes following transinfection, including genes associated with DNA replication, symbiosis, and the degenerate prophage WOAlbB.